Paradoxical Hyperexcitability in Disorders of Neurodevelopment - Antoine, Michelle W. (Frontiers in Molecular Neuroscience, 2022)
Autism Spectrum Disorder (ASD), Rett syndrome (RTT) and Angelman Syndrome (AS) are neurodevelopmental disorders (NDDs) that share several clinical characteristics, including displays of repetitive movements, developmental delays, language deficits, intellectual disability, and increased susceptibility to epilepsy. While several reviews address the biological basis of non-seizure-related ASD phenotypes, here, I highlight some shared biological mechanisms that may contribute to increased seizure susceptibility, with a focus on genetic studies identifying the anatomical origin of the seizure phenotype in loss-of-function, monogenic, mouse models of these NDDs, combined with insights gained from complementary studies quantifying levels of synaptic excitation and inhibition. Epilepsy is characterized by a sudden, abnormal increase in synchronous activity within neuronal networks, that is posited to arise from excess excitation, largely driven by the co-existence of reduced synaptic inhibition. Primarily for this reason, elevated network excitability is proposed to underlie the causal basis of ASD, RTT, and AS. Although, mouse models of these disorders replicate aspects of the human condition i.e. exhibiting either hyperexcitability discharges or seizures on cortical electroencephalograms, measures at the synaptic level often reveal deficits in excitatory synaptic transmission, rather than too much excitation. Resolving this apparent paradox has direct implications regarding expected outcomes of manipulating GABAergic tone. In particular, in NDDs associated with seizures, cortical circuits can display reduced, rather than normal or increased levels of synaptic excitation, and therefore suggested treatments aimed at increasing inhibition could further promote hypoactivity instead of normality. In this review, I highlight shared mechanisms across animal models for ASD, RTT and AS with reduced synaptic excitation that can promote hyperexcitability in cortical circuits. Namely, I discuss how cumulative effects that cause cell autonomous changes in glia and excitatory pyramidal neurons reduce synaptic inhibition levels, and how cell autonomous changes in interneurons or excitatory pyramidal neurons can promote increased intrinsic excitability in glutamatergic neurons.